Seeking the truth from mobile evidence : basic fundamentals, intermediate and advanced overview of current mobile forensic investigations - Bair, John (Academic Press, an imprint of Elsevier, 2018)
Seeking the Truth from Mobile Evidence: Basic Fundamentals, Intermediate and Advanced Overview of Current Mobile Forensic Investigations will assist those who have never collected mobile evidence and augment the work of professionals who are not currently performing advanced destructive techniques. This book is intended for any professional that is interested in pursuing work that involves mobile forensics, and is designed around the outcomes of criminal investigations that involve mobile digital evidence. Author John Bair brings to life the techniques and concepts that can assist those in the private or corporate sector. Mobile devices have always been very dynamic in nature. They have also become an integral part of our lives, and often times, a digital representation of where we are, who we communicate with and what we document around us. Because they constantly change features, allow user enabled security, and or encryption, those employed with extracting user data are often overwhelmed with the process. This book presents a complete guide to mobile device forensics, written in an easy to understand format. Provides readers with basic, intermediate, and advanced mobile forensic concepts and methodology. Thirty overall chapters which include such topics as, preventing evidence contamination, triaging devices, troubleshooting, report writing, physical memory and encoding, date and time stamps, decoding Multi-Media-Messages, decoding unsupported application data, advanced validation, water damaged phones, Joint Test Action Group (JTAG), Thermal and Non-Thermal chip removal, BGA cleaning and imaging, In-System-Programming (ISP), and more. Popular JTAG boxes - Z3X and RIFF/RIFF2 are expanded on in detail. Readers have access to the companion guide which includes additional image examples, and other useful materials.